Sustained Benefits of Acceptance and Commitment Therapy on Emotion Recognition and Mind-Body Connection - Chikwe, Chidinma; Zadhasn, Zohreh (Journal of Personality and Psychosomatic Research (JPPR), 2024)
This study aims to evaluate the effectiveness of Acceptance and Commitment Therapy (ACT) on enhancing emotion recognition and strengthening the mind-body connection. A randomized controlled trial design was employed with 30 participants randomly assigned to either an intervention group (ACT) or a control group, each consisting of 15 participants. The intervention group underwent eight 60-minute ACT sessions over eight weeks, while the control group received no intervention. Data were collected at three time points: baseline, post-intervention, and four-month follow-up, using the Emotion Recognition Questionnaire (ERQ) and the Mindful Awareness and Body Connection Scale (MABC). Data analysis involved repeated measures ANOVA and Bonferroni post-hoc tests, conducted using SPSS-27. Significant improvements were observed in the intervention group compared to the control group. For the intervention group, the mean ERQ score increased from 58.40 (SD = 6.85) at baseline to 72.30 (SD = 5.90) post-intervention, and slightly decreased to 70.50 (SD = 6.20) at follow-up. In contrast, the control group showed no significant changes, with mean ERQ scores of 57.90 (SD = 7.10) at baseline, 58.60 (SD = 6.95) post-intervention, and 57.80 (SD = 7.00) at follow-up. Repeated measures ANOVA revealed significant effects for group (F(1, 28) = 15.76, p < .001), time (F(2, 56) = 20.78, p < .001), and the interaction between time and group (F(2, 56) = 15.26, p < .001). Bonferroni post-hoc tests confirmed significant improvements in the intervention group from baseline to post-intervention (mean difference = -13.90, p < .001) and baseline to follow-up (mean difference = -12.10, p < .001). ACT significantly enhances emotion recognition and strengthens the mind-body connection. These improvements are sustained over time, highlighting ACT's potential as an effective intervention for these psychological domains.